2005
DOI: 10.2323/jgam.51.353
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mesophilic cellulose-degrading bacteria from flower stalks-vegetable waste co-composting system

Abstract: Fifteen mesophilic bacteria with high C x cellulase activities were isolated and purified from a mixed-culture enriched from a flower stalks-vegetable waste co-composting system. A CMCase test showed that the enzyme activity of these isolates ranged from 7.9 to 28.0 U ml ؊1. Although filter paper degrading capability was low in single culture, significant synergetic cellulose degradation were detected in four groups of mixed cultures, their degradation rates were 23.5%, 26.3%, 19.4% and 24.5%, respectively. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 34 publications
10
29
0
2
Order By: Relevance
“…Among the cellulolytic bacteria maximum cellulase activity was in isolate B-30 (3.48 cm) followed by isolate B-28 (2.98 cm). These results are in conformity with the results of Lu et al, (2005) who screened fifteen mesophilic bacteria which showed the ability to develop clearing zones around their colonies ranging from 2.55 to 6.40 cm. Similar results have also been reported by Ariffin et al, (2006), Shankar et al, (2011) and Majidi et al, (2011).…”
Section: Screening Of Cellulolytic Microorganismssupporting
confidence: 79%
“…Among the cellulolytic bacteria maximum cellulase activity was in isolate B-30 (3.48 cm) followed by isolate B-28 (2.98 cm). These results are in conformity with the results of Lu et al, (2005) who screened fifteen mesophilic bacteria which showed the ability to develop clearing zones around their colonies ranging from 2.55 to 6.40 cm. Similar results have also been reported by Ariffin et al, (2006), Shankar et al, (2011) and Majidi et al, (2011).…”
Section: Screening Of Cellulolytic Microorganismssupporting
confidence: 79%
“…CDB have been isolated from various environments such as compost systems [22,43], soils [1,21], wastewaters [40], and thermal springs [19]. However, to date there is no report of CDB from the deep terrestrial subsurface environments such as those exempliWed by ultra-deep mines which represents an emerging area for exploring the microbial populations with bewildering arrays of metabolic capabilities [10].…”
Section: Introductionmentioning
confidence: 98%
“…Thermophilic cellulose-degrading bacteria have been isolated from various environments such as compost systems (Lu et al, 2005;Mayendea et al, 2006;Ng et al, 2009), soils (Abdel-Fattah et al, 2007;Lee et al, 2008), wastewaters (Tai et al, 2004), and from the deep subsurface of the former Homestake gold mine in Lead, SD, now known as the NSF Deep Underground Science and Engineering Laboratory (DUSEL) (Rastogi et al, 2009a). The deep biosphere of gold mines harbors harsh environments similar to those in industrial processes for microorganisms, both natural and anthropogenic, including extreme temperature, pH, pressure, low-oxygen concentration, and inhibitors including toxic metals.…”
Section: Introductionmentioning
confidence: 99%